2014
DOI: 10.1111/gtc.12205
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of HP1γ expression during neuronal maturation promotes axonal and dendritic development in mouse embryonic neocortex

Abstract: Immature neurons undergo morphological and physiological changes including axonal and dendritic development to establish neuronal networks. As the transcriptional status changes at a large number of genes during neuronal maturation, global changes in chromatin modifiers may take place in this process. We now show that the amount of heterochromatin protein 1c (HP1c) increases during neuronal maturation in the mouse neocortex. Knockdown of HP1c suppressed axonal and dendritic development in mouse embryonic neoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Cbx3 plays important roles in developmental processes (Morikawa et al 2013). In model systems, Cbx3 promotes neuronal maturation, kidney development, differentiation of ESCs to smooth muscle in culture, and embryonic arteriogenesis (Xiao et al 2011;Dihazi et al 2015;Oshiro et al 2015). Little is known of how Cbx3 functions in differentiation, but its promoter localization suggested that it might directly affect transcription through the preinitiation complex (PIC) (Grunberg and Hahn 2013;Allen and Taatjes 2015).…”
mentioning
confidence: 99%
“…Cbx3 plays important roles in developmental processes (Morikawa et al 2013). In model systems, Cbx3 promotes neuronal maturation, kidney development, differentiation of ESCs to smooth muscle in culture, and embryonic arteriogenesis (Xiao et al 2011;Dihazi et al 2015;Oshiro et al 2015). Little is known of how Cbx3 functions in differentiation, but its promoter localization suggested that it might directly affect transcription through the preinitiation complex (PIC) (Grunberg and Hahn 2013;Allen and Taatjes 2015).…”
mentioning
confidence: 99%
“…Interestingly, a recent study demonstrated that HP1γ protein levels increase in cortical neurons of the mouse embryonic neocortex 11 . Using immunohistochemistry, this study specifically compared the cortical neurons before and after their migration from the ventricular zone.…”
Section: Resultsmentioning
confidence: 99%
“…KLF11), which are involved in the regulation of neuron specific genes, such as the Dopamine receptor D2 10 . Other groups have implicated a role of HP1γ in neuronal differentiation 11 , 12 . However, the mechanism by which HP1γ regulates neuronal cell differentiation and cell functions remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…While multiple molecular pathways including guidance cues and growth factors have been implicated in axonal development 41 , very little is known about chromatin-regulatory mechanisms 43 . Recently, the SET (histone methyltransferase) domain-containing transcriptional repressor, PRDM8, was described as essential for the formation of trans-callosal and other interhemispheric fiber tracts 44 Likewise, heterochromatin-associated protein HP1γ is required for the crossing of callosal axons into the contralateral hemisphere, while increased neuronal HP1γ expression promotes growth and differentiation of dendrites and axons 45 . Interestingly, PRDM8 promotes H3K9 methylation 46 and HP1γ is bound preferentially to compacted nucleosomal arrays bearing the repressive H3K9me3 mark 47 .…”
Section: Discussionmentioning
confidence: 99%